Modelling residual stress and residual work hardening induced by surface mechanical attrition treatment. (1st November 2022) - Zhou, Jianqiang; Cui, Kun; Xu, Zhiyuan; Sun, Zhidan; Guelorget, Bruno; Retraint, Delphine
Highlights: SMAT process on a cylindrical structure is simulated based on DEM-FEM. Generation of residual stress and its relation with work hardening are analyzed. Predicted residual stress is validated by comparing with experimental results. Residual stress generation is strongly dependent on the residual yield stress. Abstract: Shot peening induced residual stress is strongly related to residual work hardening which relies on both the process and the target material. In this work, residual stress and coupled residual work hardening are studied in a surface mechanical attrition treatment (SMAT) on a cylindrical structure by combining discrete element method (DEM) and finite element method (FEM). Shot, ultrasonic parameters, chamber structure, sonotrode surface, and cylindrical structure of the target are finely modeled in DEM simulation. On the basis of the DEM results, FEM simulation of the SMAT process is performed on a representative area considering the factual impact parameters and elastic-plastic behavior of the target material, and mechanism of residual stress generation is analyzed. It shows that isotropic hardening and kinematic hardening of the target material play a different role in residual stress generation. The obtained maximum compressive residual stress is mainly determined by residual yield stress, while the residual kinematic hardening is nearly unchanged when the coverage is increased. Further analyses indicate that the mechanisms of residual stress generation should be very different for the Johnson-Cook model and the model that includes kinematic hardening, even though these two kinds of models are reported to be able to well predict the shot peening induced residual stress. The gradient of the residual work hardening can be used for further evaluating mechanical properties of the SMATed cylindrical structure. Graphical abstract: Image, graphical abstract